Development of a protocol for Malaysian Important Plant Areas criterion weights using Multi-criteria Decision Making - Analytical Hierarchy Process (MCDM-AHP) - Hamidah, M.; Mohd Hasmadi, I.; Chua, L. S. L.; Yong, W. S. Y.; Lau, K. H.; I., Faridah Hanum; Pakhriazad, H. Z. (Elsevier, 2022)
Globally, in the selection of potential Important Plant Areas (IPAs), the preferred method used is scoring method because of its simplicity and ease of evaluation. However, the criterion weights developed from this method are vague and suffer from judgement uncertainties. In this study, we developed and propose a methodology for the assessment of Malaysian IPA criterion weights using Multi-Criteria Decision Making (MCDM) - Analytical Hierarchy Process (AHP). The criterion weights were assessed from data obtained through questionnaire surveys of Malaysian biodiversity experts. As a result, threatened habitats are given the highest score (0.337), followed by threatened species (0.327), endemism (0.245), and botanical richness (0.091). This study, therefore, proposes the MCDM-AHP as a decision-making tool for prioritising and formulating criterion weights for Malaysian IPA.